Analysis of Nursing Care for the Elderly with the Application of Warm Cinnamon Compress Therapy to Reduce Pain in Gout Arthritis - Annisa Miftahul Rizqa; Siska Mayang Sari; Eka Wisanti; Yumiati (Journal of Health Empowerment and Interprofessional Practice, 2026)
Elderly individuals are individuals aged 60 years and above and are susceptible to various health problems, one of which is gout arthritis, a metabolic disorder caused by excess uric acid buildup that causes joint pain. Pain experienced by the elderly can interfere with comfort and daily activities, so appropriate nursing interventions are needed, including non-pharmacological approaches. This scientific paper aims to analyze nursing care for Mrs. M and Mr. A and evaluate the application of cinnamon warm compress therapy in reducing gout arthritis pain in the elderly at the UPT PSTW Husnul Khotimah, Riau Provincial Social Service, according to professional nursing standards. The method used is a one-group pretest-posttest design with two subjects. The instrument used is a pain scale observation sheet. The cinnamon warm compress intervention was given for 15 minutes every day at 14.00–15.00 WIB during the period of November 29 to December 5, 2025. The results showed that the average pain scale before the intervention was 4.8 and after the intervention decreased to 3, with an average pain reduction of 1.7 for seven days. It was concluded that cinnamon warm compress therapy was effective in reducing gout arthritis pain and can be recommended as a non-pharmacological intervention in nursing care for the elderly with routine pain monitoring.